The Biophysical Properties of the Fruit Cuticles of Six Pear Cultivars during Postharvest Ripening - Klemen Bohinc; Petra Lasić; Nives Matijaković Mlinarić; Filip Šupljika; Blažka Smolič; Anže Abram; Ivan Jerman; Nigel Willy Van de Velde; Marjeta Mencin; Mojca Bavcon Kralj; Rajko Vidrih (Agronomy, 2024)
Pears are abundant in bioactive compounds, which exert favorable effects on human health. The biophysical attributes of fruit cuticles are pivotal in determining fruit quality, storability, and susceptibility to mold growth. This study aimed to elucidate the biophysical properties of six pear cultivars, ‘Conference’, ‘Celina’, ‘Abate Fetel’, ‘Packham’s Triumph’, ‘Sweet Sensation’, and ‘Williams’. Two maturity stages, unripe and fully ripened, were investigated. Furthermore, the efficacy of trimethyl-chitosan-coated pear surfaces in preventing Penicillium expansum (P. expansum) growth was assessed. Basic maturity indices (CIE color, ethylene evolution, firmness, soluble solids), cuticle contact angle, roughness, and zeta potential were analyzed. Surface roughness was measured using an optical profilometer, hydrophobicity was measured via profilometry, and zeta potential was quantified using an electrokinetic analyzer. The ‘Celina’ cultivar exhibited the highest roughness, whereas ‘Williams’ had the lowest roughness. All the cultivars’ cuticles demonstrated hydrophilic characteristics, with contact angles ranging between 65° and 90°. For pH values exceeding 3.5, all pear surfaces exhibited a negative zeta potential. P. expansum growth was the slowest on the ‘Packham’s Triumph’ and ‘Conference’ cultivars. Treatment with trimethyl chitosan effectively inhibited P. expansum growth in the initial hours of incubation. In conclusion, diverse pear cultivars manifest distinct biophysical surface properties and varying susceptibility to P. expansum growth. The growth of P. expansum correlates positively with roughness, contact angle, and zeta potential. These differences can significantly impact shelf life potential and the overall postharvest quality of pears.